ANALISIS MANAJEMEN RISIKO PEMELIHARAAN DAN KALIBRASI ALAT OPERASIONAL UTAMA DI BADAN METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA - Putra, Maulana (JURNAL ILMIAH EDUNOMIKA, 2025)
Uncertainty in the operational and strategic aspects of an organization requires management to implement risk management. This study aims to identify, analyze, and manage risks arising during the maintenance and calibration processes of Main Operational Equipment at the Meteorology, Climatology, and Geophysics Agency. The methods include risk identification using a quantitative approach, impact and likelihood analysis, development of control strategies, and monitoring. The results show key risk statements, including spare parts limitations and workplace accidents, which can affect strategic performance targets as well as health and safety. Control measures can be implemented through improved coordination, regular training, and audits monitored by risk managers, risk management units, and internal audit units.